2463. Post-licensure Surveillance of 9-Valent Human Papillomavirus Vaccine (9vHPV) in the Vaccine Adverse Event Reporting System (VAERS), United States, 2014–2017. (26th November 2018) - Arana, Jorge; Su, John; Lewis, Paige; Cano, Maria; Markowitz, Lauri E; Shimabukuro, Tom
Abstract: Background: 9-valent human papillomavirus vaccine (9vHPV) was licensed in December 2014 and recommended by the Advisory Committee on Immunization Practices (ACIP) in February 2015. 9vHPV is FDA-approved for females and males aged 9–26 years; ACIP recommends routine vaccination at 11–12 years and through age 26 for women and 21 for males. About 29 million doses of 9vHPV were distributed in the United States through the end of 2017. We analyzed the first 3 years of US post-licensure safety data in the Vaccine Adverse Event Reporting System (VAERS). Methods: We searched VAERS, a spontaneous reporting system, for US reports of adverse events (AEs) following 9vHPV from December 1, 2014 to December 31, 2017. We conducted descriptive analysis of reports and assessed the most common signs and symptoms of AEs. Physicians reviewed reports and available medical records for reports classified as serious (death, life-threatening illness, hospitalization, prolongation of hospitalization and permanent disability) and for selected pre-specified conditions of interest. Results: VAERS received 7, 244 reports following 9vHPV; 186 (2.6%) were classified as serious. In 5, 411 (74.7%), 9vHPV was administered alone. The most frequently reported symptoms were dizziness (579; 8.0%), syncope (517; 7.1%), headache (418; 5.8%), nausea (361; 5.0%), and injection site pain (324; 4.5%). Median time from vaccination to symptom onset was <1 day (range 0–751 days). There were 7 (0.1%) death reports; 2 verified from autopsy report, death certificate, and/or medical records (causes of death were cardiac arrest and cerebellar aneurysm) and 5 "hearsay" reports with no verifiable medical information. Reports of selected pre-specified conditions of interest included anaphylaxis (9; 0.1%), Guillain–Barré syndrome (8; 0.1%), postural orthostatic tachycardia syndrome (17; 0.2%), primary ovarian insufficiency (3; <0.1%), and complex regional pain syndrome (1; <0.1%). No unusual clustering around onset interval was observed. Conclusion: In our VAERS review, the safety profile of 9vHPV was consistent with that observed from pre-licensure clinical trials and from post-licensure safety monitoring of other HPV vaccines. We did not observe any new safety signals or unexpected patterns of AEs. Disclosures: All authors: No reported disclosures.